1997
DOI: 10.1111/j.1651-2227.1997.tb08602.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of behavioral and affective patterns in girls with central precocious puberty during long‐acting triptorelin therapy

Abstract: and Lit?ge6, Belgium, in collaboration with the Belgiun Sritdy Group f;) r Pediatric Endocrinology ' Xhrouet-Heinrichs D, Lagrou K, Heinrichs C, Craen M, Dooms L, Malvaux P, Kanen F, Bourguignon J-P. Longitudinal study of behavioral and affective patterns in girls with central precocious puberty during longacting triptorelin therapy. Acta Pzdiatr 1997; 86: 808-15. Stockholm. ISSN 0803-5253The aim of the present study was to evaluate the behavioral and affective characteristics and the changes in psychosocial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 24 publications
2
37
1
4
Order By: Relevance
“…Precocious and early-onset puberty is frequently associated with psychological and behavioral problems in childhood and may aggravate the feeling of being different from peers [59,60]. In our cohort we found significantly lower height in adopted girls compared to their Danish peers in all age groups – a difference that might be enhanced by early onset of puberty, which was also indicated in our cohort by advancement in BA in early maturing girls [61].…”
Section: Discussionsupporting
confidence: 66%
“…Precocious and early-onset puberty is frequently associated with psychological and behavioral problems in childhood and may aggravate the feeling of being different from peers [59,60]. In our cohort we found significantly lower height in adopted girls compared to their Danish peers in all age groups – a difference that might be enhanced by early onset of puberty, which was also indicated in our cohort by advancement in BA in early maturing girls [61].…”
Section: Discussionsupporting
confidence: 66%
“…How common these issues are in girls with PA and whether they change over time has likewise not been explored. While parental distress secondary to a child’s early puberty has also been reported, whether mothers of all girls with forms of precocious puberty experience psychological difficulty has not been examined [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Reviews of studies of girls with untreated precocious puberty 34,37,38 concluded that age-appropriate psychosocial and psychosexual adjustment were commonly achieved; however controlled studies were limited. Characteristic personality traits of the girls with untreated or treated 35,[39][40][41] precocious puberty included poor self-image and internalizing symptoms.…”
Section: Iq and Psychopathologymentioning
confidence: 99%